Structure determination of disease associated peak AAA from l-Tryptophan implicated in the eosinophilia-myalgia syndrome. (5th January 2018) - Klarskov, Klaus; Gagnon, Hugo; Boudreault, Pierre-Luc; Normandin, Chad; Plancq, Baptiste; Marsault, Eric; Gleich, Gerald J.; Naylor, Stephen
Highlights: The final EMS case-associated contaminant, Peak AAA ofl -Tryptophan identified. Peak AAA shown to be two different structural isomers. Identified as two condensation products of L-Tryptophan with isomeric fatty acids. They possess very different properties from other 5 case associated contaminants. Abstract: The eosinophilia-myalgia syndrome (EMS) outbreak of 1989 that occurred in the USA and elsewhere was caused by the ingestion ofl -Tryptophan (L-Trp) solely manufactured by the Japanese company Showa Denko K.K. (SD). Six compounds present in the SD L-Trp were reported to be case-associated contaminants. However, "one" of these compounds, Peak AAA has remained structurally uncharacterized, despite the fact that it was described as "the only statistically significant (p = 0.0014) contaminant". Here, we employ on-line microcapillary-high performance liquid chromatography-electrospray ionization mass spectrometry (LC–MS), and tandem mass spectrometry (MS/MS) to determine that Peak AAA is in fact two structurally related isomers. Peak AAA1 and Peak AAA2 differed in LC retention times, and were determined by accurate mass-LC–MS to both have a protonated molecular ion (MH +) of mass 343.239 Da (Da), corresponding to a molecular formula of C21 H30 N2 O2, and possessing eight degrees of unsaturation (DoU) for the non-protonated molecule. By comparing the LC–MS and LC–MS-MS retention times and spectra with authentic synthetic standards, Peak AAA1 was identified as the intermolecular condensation product of L-Trp with anteiso 7-methylnonanoic acid, to afford ( S )-2-amino-3-(2-((S, E)-7-methylnon-1-en-1-yl)-1H-indol-3-yl)propanoic acid. Peak AAA2 was determined to be a condensation product of L-Trp with decanoic acid, which produced ( S )-2-amino-3-(2-(( E )-dec-1-en-1-yl)-1H-indol-3-yl)propanoic acid.